Creating The Framework For Strategic Planning For The Development Of Private Universities: An Independent Study Based On Private Education In Vietnam - Phuong Le , Thi Mai; Duraipandi, Oyyappan (Cuestiones de Fisioterapia, 2023)
Strategic planning and the growth of vietnam's private universities were the subjects of this research. It looked at how the further educational industry benefited from more organised planned procedures in terms of development, longevity, and competition. A quantitative research approach was used to obtain data from a significant sample of people via the use of a structured questionnaire. The demographics and structural features were described using descriptive statistics, were conducted using modelling of variance and factor analysis. The results showed that private institutions' progress was greatly impacted by strategic planning, especially about educational excellence, faculty ability, customer amenities, and infrastructural growth. Structured planned organisations also fared better in adapting to regulatory changes, financial swings, and internationalisation, according to the data. University strategic planning also helped in attracting funds, improving competitiveness with private and foreign organisations, and aligning capabilities with prospective goals. The analytical data strongly suggested that strategic planning was a key factor in the rise of private universities, thereby rejecting the null hypothesis. The research found that private organisations ran the danger of uncontrolled expansion, resources constraints, and diminished efficiency in the absence of organised management. Consequently, private universities in vietnam may respond to shifting circumstances and achieve national growth objectives with the help of strategic planning, which is a vital enabler of longevity, adaptability, and scholarly success. Through the facilitation of sustainable growth strategies that were in line with national academic objectives, the research showed that strategic planning enhanced organisational resiliency. Because of the findings, community participation is critical for comprehensive and adaptable planning.